Human enhancement and perfection. Issue 10 (22nd February 2013) - Roduit, Johann A R; Baumann, Holger; Heilinger, Jan-Christoph
Abstract : Both, bioconservatives and bioliberals, should seek a discussion about ideas of human perfection, making explicit their underlying assumptions about what makes for a good human life. This is relevant, because these basic, and often implicit ideas, inform and influence judgements and choices about human enhancement interventions. Both neglect, and polemical but inconsistent use of the complex ideas of perfection are leading to confusion within the ethical debate about human enhancement interventions, that can be avoided by tackling the notion of perfection directly. In the recent debates, bioconservatives have prominently argued against the 'pursuit of perfection' by biotechnological means. In the first part of this paper, we show that—paradoxically—bioconservatives themselves explicitly embrace specific conceptions of human perfection and perfectionist assumptions about the good human life in order to argue against the use of enhancement technologies. Yet, we argue that the bioconservative position contains an untenable ambiguity between criticising and endorsing ideas of human perfection. Hence, they stand in need of clarifying their stance on human perfection. In the second part of the paper, we ask whether bioliberals in fact (implicitly) advocate a particular conception of perfection, or whether they are right in holding that they do not, and that discussing perfection is obsolete anyway. We show that bioliberals also rely on a specific idea of human perfection, based on the idea of autonomy. Hence, their denial of the relevance of perfection in the debate is unconvincing and has to be revised.